PSYCHOLOGICAL AND PEDAGOGICAL BASIS OF MANAGEMENT ACTIVITIES IN VOCATIONAL EDUCATION INSTITUTIONS - Гергун, В.А. (SWorldJournal, 2025)
The article presents an understanding of the essence of management, stages of management activity. The presence of a branched structure of management bodies in vocational education institutions requires the organization of their interaction, coordination